(untitled) (Applied Biological Research, 2013)
The present study, conducted at the Experimental Farm, Division of FMAP, SKUAST-Kashmir, Shalimar, was aimed at to evaluate the effect of three nitrogen levels (50, 75 and 100 kg ha-1), two phosphorus levels (100 and 125 kg ha-1) and three biofertilizers (Bacillus sp., Pseudomonas sp. and Azotobacter sp.) on vegetative and floral characteristics of dahlia (Dahlia variabilies Desf.) cv. ‘Pink Attraction’. Amongst the nitrogen treatments, 50 kg N ha-1application resulted in minimum number of days for tuber emergence, days for 1st floral bud appearance, days to full opening of 1st flower but longer flowering duration. Further, maximumplant height, number of primary branches plant-1, length of primary branches, leaf area and flower diameter, highest fresh flower weight and longest vase life was observed in treatment 75 kg N ha-1. In comparison to 125 kg P ha-1treatment, the application of 100 kg P ha-1resulted in early tuber sprouting and 1st floral bud appearance with maximum plant height, flower diameter, peduncle length, blooming period, flower number plant-1, fresh flower weight and flower vase life. Amongst the biofertilisers, Azotobacter proved superior in improving plant height, length of primary branches, flower diameter, peduncle length and number of flowers plant–1. The interaction of three factors was significant. The 1st order interaction among N, P and biofertilizers were significant for several vegetative and floral characters. The use of N75P100, N75 + Azotobacter and P100 + Azotobacter showed significant improvement in various growth and flower parameters. Of the all treatment combinations evaluated, the application of 75 kg N ha-1+ 100 kg P ha-1+ Azotobacter gave maximum plant height (77.98 cm), number of primary branches plant-1(10.53), length of primary branches (58.55 cm), leaf area (88.33 cm2), flower diameter (10.31 cm), flowering duration (101.73 day), flower fresh weight (17.82 g flower-1) and longest vase life (5.93 days).